Kuhn’s Paradigm in Action: Is Robotic Process Automation Reshaping Accounting Norms? - Perwitasari, Dian; Iswati, Sri (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
The development of science causes a shift from the old to the new paradigm. With his term “scientific revolution”, Kuhn proposed a more radical and revolutionary paradigm shift in science. This study aims to explore the relevance of RPA (and AI within it) from Kuhn's perspective, identify the opportunities and challenges of RPA according to the scientific community's perception, and RPA in the future for accounting firms. The method used in this research is descriptive-qualitative, which collects detailed data from various literature and semi-structured interviews. Our findings highlight that RPA becomes an inclusive and sustainable transformation tool with the right approach, providing broad economic and social benefits without compromising ethics. Policymakers should encourage collaboration between technology and the accounting profession. The presence of RPA is not a substitute for the accounting profession. There needs to be guidelines for using RPA balanced with establishing governance standards that emphasize the importance of accountability for the results processed by automated systems.